Spider XFEM, an extended finite element variant for partially unknown crack-tip displacement - Chahine, Elie; Laborde, Patrick; Renard, Yves (European Journal of Computational Mechanics, 2008)
In this paper, we introduce a new variant of the extended finite element method (Xfem) allowing an optimal convergence rate when the asymptotic displacement is partially unknown at the crack tip. This variant consists in the addition of an adapted discretization of the asymptotic displacement. We give a mathematical result of quasi-optimal a priori error estimate which allows to analyze the potentialities of the method. Some computational tests are provided and a comparison is made with the classical Xfem.